Reducing primary dysmenorrhea among adolescent girls with mung bean extract drinks and stretching - Baiq Dewi Sukma Septiani; Adi Prayitno; Sugiarto Sugiarto (Intelektual Pustaka Media Utama, 2019)
Primary dysmenorrhea is pain during menstruation period due to high levels of prostaglandins, especially prostaglandin F2α in epithelial cells. MungBean Extract Drinks contain several nutrients including vitamin C, calcium, carbohydrates and flavonoids as anti-depressants and anti-inflammatory agent. Stretching is a relaxation technique that can helps relieve menstrual pain in the abdominal part by increasing the production of endorphins which function as neurotransmitters. To determine the effect of Mung Bean ExtractDrinks and Stretching on primary dysmenorrhea (primary menstrual pain) in adolescent girls stressed. This type of open-label non-randomized controlled trial used 87female adolescents who experienced primary menstrual pain with moderate and severe stress levels from two Islamic boarding schools in Mataram City, West Nusa Tenggara, Indonesia, which were divided into 3 groups, one group as the control and two groups as the experiment. The experiment of 29people with pre and post-test. Mung bean extract drinks were given 250ml/day, otherwise stretching was given 1x/day for 7days before menstruation. Control and experimental group was observed for 1 month. Measurement of menstrual pain scale using the Numeric Rating Scale (NRS) assessment sheet. Data analysis uses T-test. The mean primary menstrual pain in adolescents for MungBean Extract Drinks with moderate stress levels was 1.31±1.32 and the difference before and after mung bean extract drinks experience is significant at p=0.004 while at severe stress levels was 1.69±1.54 and the difference between before and after mung bean extract drinks experience is significant at p=0.001. The mean primary menstrual pain in adolescents for stretching experience with moderate stress levels was 2.50±1.93 and the difference before and after stretching experience is significant at p=0.008 while the severe stress level was 2.05±1.80 and the difference before and after stretching experience is significant at p≤0.001. The multivariate test with linear regression revealed that mung bean extract drinks contributed y= (-)138X1+4.897(p=0.001) and related stretching contributed y= (-)2.517X1+6.276(p=0.001). MungBean ExtractDrinks and Stretching will affect to the reduction of primary dysmenorrhea in adolescent girls both at moderate and severe stress levels